Asymmetric Mannich Reaction of Fluorinated Ketoesters with a Tryptophan-Derived Bifunctional Thiourea Catalyst - Han, Xiao; Kwiatkowski, Jacek; Xue, Feng; Huang, Kuo-Wei; Lu, Yixin (Angewandte Chemie International Edition, 2009)
Fluorinated quaternary stereocenters: A novel bifunctional catalyst 1 derived from natural tryptophan promoted the Mannich reaction of α‐fluoro‐β‐ketoesters to afford fluorinated chiral molecules containing vicinal quaternary and tertiary stereogenic centers with exceptional enantioselectivity. An unprecedented α‐fluoro‐β‐lactam was also prepared by this method (see scheme; Boc=tert‐butoxycarbonyl).